Ženske dvojinske glagolske oblike v starejšem slovenskem knjižnem jeziku - Orel, Irena (Slavistična revija, 2019)
The article deals with secondary feminine dual verb forms that passed from spoken use into the older, literary language from the sixteenth century onwards, with a decline in the seventeenth and eighteenth centuries, and a renewal in the nineteenth century, when they once again had a presence in texts and were standardized in grammar until they were abandoned at the beginning of the twentieth century. A review of the expert literature, grammar books, selected texts, and (historical) corpuses reveals the use, normativity, and interpretation of this older innovation of the literary language.
Keywords: dual; dvojina; glagol; govorjeni jezik; grammar; historical morphology; normativity; normativnost; razcep po spolu; Slovenian language; slovenščina; slovnice; spoken language; the gender split; verb; zgodovinsko oblikoslovje